Abdij van Park (2024)
Keywords: park

Mozes en zijn broer Aaron : een buitengewone cyclus 13de-eeuwse muurschilderingen ontdekt in de kapittelzaal van de Parkabdij - Bergmans, Anna; De Clercq, Lode; Lagaert, Joke (M&L: Monumenten en Landschappen, 2022)
Moses and his brother Aaron. The discovery of an exceptional cycle of 13th-century wall paintings in Park Abbey’s chapter house The Premonstratensian Park Abbey in Heverlee (Leuven) has already been studied and restored for many years. With each interior intervention, there have been major surprises. In 2017, during ongoing preliminary investigations, the city of Leuven ordered some additional probes for the chapter house, mainly to locate the original access to this room from the cloister. This research soon led to the discovery of painted fragments, which then asked for more extensive studies. Here, the entire original space of the chapter house was involved. Some very fine remains of a unique decor were thus revealed. This discovery offers a completely new dimension to the chapter house of Park Abbey, which is unique in Belgium. The east wing of the cloister, in which the chapter house is located, was built in the same period as the western part of the church, namely the second half of the 13th century. During the 16th century the chapter house was thoroughly rebuilt and redecorated. However, the preliminary investigation showed that there were still considerable fragments of medieval murals on the walls. On the western wall, several biblical figures can be distinguished. Moses with the tablets of the law points to the idolatrous dragon-like devil on a pillar. To his right stands his brother Aaron holding his attribute, a flaming fire. Next to him appears their sister Myriam. A little further north, the bearded man may be one of the Three Kings. These figures point to a cycle evolving from Old to New Testament with Biblical characters as prefigures. Also very beautiful is the preserved architectural polychromy on the Gothic openings between the cloister and the chapter house. On the east wall, among other things, there are some beautiful fragments of painted frames around closed oculi. The painted ensemble, dating from the second half of the 13th century, is designed as a whole, both iconographically and in terms of style and technique. The figures in the upper register are framed with a monumental frieze. In this way, a continuous band with figures was created. The extent of the paintings and the rather good condition in which they have been preserved, make the Park Abbey’s chapter house quite exceptional and unique. In view of the future museum function of the abbey complex, the presentation of these to the public will be of great value.
Number: 2
Keywords: park

Vroege receptiesporen van Van den vos Reynaerde en Spiegel historiael op een onbekend fragment in de Abdij van Park (Heverlee, Archief Abdij van Park, VIIIB20/120) - Breeus-Loos, Laurent; Van Eldere, Irene (Spiegel der letteren, 2022)
Keywords: park

Het Missaal van Park (Oxford, Wadham College, Ms. A.14.12). Een liturgisch boek in opdracht van Ambroos van Engelen, abt van Park - Kügle, Karl (Als de bliksem. 900 jaar norbertijnen en norbertinessen, 2021)
Keywords: park

'Scriptus est liber iste in honore Sanctae Mariae in Parcho'. De Parkbijbel uit 1148 - Macarenko, Aleuna (Als de bliksem. 900 jaar norbertijnen en norbertinessen, 2021)
Keywords: park

Indrukwekkende reeks glasramen van Jan de Caumont voor de pandgang van de Parkabdij - Rambaut, Aletta (Als de bliksem. 900 jaar norbertijnen en norbertinessen, 2021)
Keywords: park

'Vrije conste dewelcke nyet gemeyns en heeft met eenige andere ambachten'. Jan Christiaan Hansche in de Parkabdij - Van Vaeck, Marco (Als de bliksem. 900 jaar norbertijnen en norbertinessen, 2021)
Keywords: park

De abdij van Park en haar abdijdomein, van Haspengouw tot Noord-Brabant - Van Lani, Stefan (Premonstratenzers en premonstratenzerinnen in Brabant, 2019)
Pages: 38-48
Keywords: park

De abdij van Park in het kaartboek van 1665 - Van Lani, Stefan (Ex abundantia cordis. Vriendenboek Mark Derez, 2019)
Pages: 41-42
Keywords: park

More stained glass fragments from Park Abbey (Leuven) discovered in Quebec - LaBrecque, Claire (Vidimus, 2018)
Keywords: park

La mobilité d'un abbé au XVe siècle. Itinéraires et liens de communications de Thierry de Tuldel - Appelmans, Janick (Mobilité et stabilité chez les Prémontrés. Guerres, catastrophes et calamités. Actes officiels des 38e et 39e colloques du Centre d'Études et de Recherches Prémontrées. Amiens, 2012 - Troyes 2013, 2018)
Keywords: park

Parkbier - Magnus, Kristiaan (Bier brouwen in Brabant tot aan de Franse tijd in het bijzonder in de norbertijinenabdijen, 2017)
Keywords: park

Stained Glass from the Corcoran Gallery to Return to Park Abbey - Shortell, Ellen M. (Vidimus, 2015)
Keywords: park

Future of Park Abbey Windows Unclear (Vidimus, 2014)
Keywords: park

De abdij van Park en haar historische bibliotheek - Lani, Stefan van (Bibliotheek van de Abdij van Park, 2014)
Keywords: park

Bibliotheek van de Abdij van Park - Van Bragt, Jozefa (Peeters, 2014)
Keywords: park

De politieke context van het premonstratenzer Iter Italicum: de Romereizen van Diederik van Tuldel (°1419-†1494) - Appelmans, Janick (Reizen in woelige tijden, 2012)
Keywords: park

De pastorie van Wakkerzeel. Een parel uit het netwerk van pastoorshuizen van de norbertijnen-abdij van Park in Vlaams-Brabant - Lani, Stefan van (Haachts oudheid- en geschiedkundig tijdschrift, 2012)
Keywords: park

Visionary Saints in the Gilded Age: The American Afterlife of the Park Abbey Glass - Shortell, Ellen M. (Collections of Stained Glass and their Histories, Transactions of the 25th International Colloquium of the Corpus Vitrearum in Saint Petersburg, The State Hermitage Museum, 2010, 2012)
Keywords: park

Liturgische handschriften met muzieknotatie in de premonstratenzer abdijen Grimbergen, Tongerlo, Park en Averbode: wat is voorhanden en welke zijn premonstratenzer handschriften? - Behrendt, Inga (Premonstratenzer gregoriaans in de Nederlanden : liturgische handschriften (13de-16de eeuw), 2011)
Keywords: averbode; grimbergen; park; tongerlo

The Incunabula of Parc Abbey (Heverlee, Leuven) - Coppens, Christian (De Gulden Passer, 2010)
Keywords: park

Een onbekend handschrift met evangeliepreken uit de tekstgroep Zwolle - Ermens, Daniël (Ons geestelijk erf, 2010)
Keywords: park

Les avatars des manuscrits médiévaux de l'abbaye de Parc - Van Balberghe, Emile (De Gulden Passer. Tijdschrift voor Boekwetenschap, 2010)
Keywords: park

De norbertijnenabdij van Park-Heverlee en haar netwerk van pastorieën - Van Lani, Stefan (Norbertijnse pastorieën in het hertogdom Brabant, 2010)
Keywords: park

Typisch norbertijns erfgoed: de pastorieën van de abdij van Park in Vlaams-Brabant - Lani, Stefan van (Haachts oudheid- en geschiedkundig tijdschrift, 2009)
Keywords: park

De Abdij van Park. Een eeuwenoude erfgoedsite van internationaal belang - Lani, Stefan van (In Godsnaam! Duizend jaar kloosters, 2007)
Keywords: park

L'Abbaye norbertine du Parc: un site unique du patrimoine à la lisière de la ville de Louvain - Van Lani, Stefan (Thiérache Développement, 2007)
OCLC: 275278536
Keywords: park

L'art de choisir ses objectifs: la stratégie politique de Thierry de Tuldel, abbé de Parc (1462-1494) - Appelmans, Janick (Abbatiat et abbés dans l?ordre de Prémontré, 2005)
Keywords: park

Chaos in the scriptorium: the Parc Bible of 1263 - Oliver, Judith H. ("Als ich can": Liber amicorum in memory of Professor Dr. Maurits Smeyers, 2002)
Keywords: park

Abt Diederik van Tuldel (°1419-†1494): een canonist in theorie en praktijk - Appelmans, Janick (Norbertijnen en wetenschap, 2001)
Keywords: park

Thierry de Tuldel et les Prémontrés brabançons face à la commende (1470-1481) - Appelmans, Janick (Analecta Praemonstratensia, 2000)
During the later middle ages holding an abbey in commendam meant that is was granted to a secular clergyman, for example a bishop, a dean or a secular canon. At Saint Michael's abbey in Antwerp as well as in Tongerlo these commendators were influential members of the Burgundian court and high-ranking ecclesiastical officials. These princes of the church gave the duke more control over his clergymen and were in return provided with a substantially increased income. Ferry de Clugny made at Tongerlo in the years 1470-1471 the first successful intrusion in a Premonstratensian monastery in Brabant. His aspirations could be bought off by a lifelong rent. Diederik van Tuldel (1419-1494), the abbot of Park since 1462, undertook different diplomatic initiatives at the papal court in order to safeguard the Brabantine abbeys from more commendators. Despite many apostolic letters and guarantees his efforts were vain. In 1477 two bishops were appointed as the heads of the communities of Antwerp and Tongerlo. The reign of the commendatory prelates started at an ill fated moment, just a few weeks after the death of Duke Charles the Bold. The central government was not able any longer to support firmly the commendators in their struggle to obtain their offices and revenues. In contrast to the many collations of Benedictine abbeys in commendam the princes of the church faced well-informed and organized opponents. At several times the different Brabantine abbots gathered to discuss the state of affairs and took action against the commendators. Diederik van Tuldel and his fellow prelates knew every move of the secular abbots and their supporters. Therefore the abbot of Park could rely upon a network of trustful informers and skilled negotiators, including abbots and Premonstratensian delegates as well as merchants and church officials at the papal court. The last commendator finally resigned in 1481, but it had necessitated many funds to compel the secular abbots to desist from their prerogatives. Since his journey to Rome in 1475 Diederik van Tuldel had co-ordinated the defense of the liberties and rights of Saint Norbert's order and had taken care of the financial settlements. With the repetitive, but sometimes reluctant, consent of the order's general chapter the taille, a taxation within the order, was used. It lasted almost fifteen years before all the debts were reimbursed.
Keywords: park; 🇧🇪 belgium (general)

Abdij van 't Park : pachthoeven en landbouwdomein - Lani, Stefan van (VZW Vrienden van Abdij van 't Park, 1999)
Keywords: park

De "Oude Molen" van Vossem - De Séjournet-Van Rijckevorsel, Marie-Elizabeth (De woonstede door de eeuwen heen: Tijdschrift van de Koninklijke Vereiniging der Historische Woosteden van België en van de Stichting Tot behouden van Particuliere Historische Bwtenplaatsen en de Nederlandse Kastelenstichting, 1998)
Surveys the history of the watermill originally belonging to the Premonstratensian Park Abbey at Leuven (Heverlee)
Keywords: park

Le rôle des méthodes de laboratoire dans le recherche de la provenance de dinanderies médiévales. Application aux fonts baptismaux de Tirlemont, aux chandeliers des abbayes de Postel et de Parc des Musées Royaux d'Art et d'Histoire de Bruxelles et aux fonts baptismaux de Saint-Barthélemy à Liège - Martinot, L. (Académie royale de Belgique: Bulletin de la classe des beaux-arts, 1997)
Keywords: park

Der Osterleuchter von Parc und Fragen der Lokalisierung romanischer Bronzen zwischen Maasgebiet und Niedersachsen - Mende, Ursula (Bulletin des Musées royaux d'art et d'histoire, 1996)
Keywords: park

Dubbels van de typografieboeken A en B van de abdij van Park in het Algemeen Rijksarchief te Brussel: een vijfde groot kaartboek van de hand van Joris en Guilliam Subil? - Janssens, Luc (Analecta Praemonstratensia, 1994)
Keywords: park

Les manuscrits médiévaux de l'Abbaye de Parc. Recueil d'articles - Balberghe, Emile van (Libraire Alain Ferraton, 1992)
Keywords: park

Etude technologique des dinanderies coulées. 2: Les fonts baptismaux de Saint-Germain à Tirlemont (1149). 3: Le chandelier pascal de l'abbaye de Postel (XIIe s.). 4: Le chandelier pascal de l'abbaye de Parc (XIIIe s.) - De Ruette, Monique (Bulletin des Musées royaux d'art et d'histoire, 1987)
Keywords: park; postel

La cession des dîmes de Cella à l'abbaye du Parc - Delforge, A. (Cella, 1985)
Keywords: park

A propos de quelques manuscrits de l'abbaye de Parc conservés à la Bibliothèque de l'Université de Gand. - Van Acker, Kamiel G. (Archives et bibliothèques de Belgique / Archief- en bibliotheekwezen in België, 1974)
Keywords: park

Les critères de provenance des manuscrits de Parc - Van Balberghe, Emile (Contributions à l'histoire des bibliothèques et de la lecture aux Pays-Bas avant 1600: Studies over het Boekenbezit en Boekengebruik in de Nederlanden vóór 1600, 1974)
Num Pages: 636 Pp.
Keywords: park

Un manuscrit universitaire padouan à l'abbaye de Parc - Fransen, Gérard (Mélanges offerts à Pierre Andrieu Guitrancourt, 1973)
Num Pages: 976 Pp.
Keywords: park

Het landbouwdomein van de abdij van Park-Heverlee - Maes, S. F.; Gerits, Trudo (Ons heem, 1973)
Keywords: park

Un catalogue des manuscrits de Parc rédigé sous Joseph II - Van Balberghe, Emile (Analecta Praemonstratensia, 1973)
Keywords: park

De oude glasramen van de Abdij van 't Park te Heverlee - Maes, F. (Jaarboek van de geschied- en oudheidkundige kring voor Leuven en omgeving, 1972)
Keywords: park

De pachthoven en de watermolen van de abdij van Park te Bertem - De Kempeneer, Joseph (Mededelingen van de Geschied- en Oudheidkundige Kring voor Leuven en Omgeving, 1970)
Keywords: park

Het register der beneficiën en kerken van de abdij van Park - De Kempeneer, Joseph (Mededelingen van de Geschied- en Oudheidkundige Kring voor Leuven en Omgeving, 1970)
Keywords: park

Deux manuscrits de Parc retrouvés - Van Balberghe, Emile (Analecta Praemonstratensia, 1970)
Keywords: park

Fragmenta Parcensia. A propos d'un fragment de la chronique dite de Saint Jérôme - Van Balberghe, Emile (Archives et bibliothèques de Belgique, 1970)
Keywords: park

Het register der beneficiën en kerken van de abdij van Park - De Kempeneer, Joseph (Mededelingen van de Geschied- en Oudheidkundige Kring voor Leuven en Omgeving, 1969)
Keywords: park

Het register der beneficiën en kerken van de abdij van Park - De Kempeneer, Joseph (Mededelingen van de Geschied- en Oudheidkundige Kring voor Leuven en Omgeving, 1968)
Keywords: park

Jacob Clinkart (gest. 1383) kopiist en prior van de abdij van Park - Brounts, Albert (Analecta Praemonstratensia, 1967)
Keywords: park

Un relevé des manuscrits de Parc conservés à la Bibliothèque de l'Université de Louvain avant 1914 - Van Balberghe, Emile (Analecta Praemonstratensia, 1967)
Keywords: park

Extraits du nécrologie de l'Abbaye du Parc - Vander Linden, Albert (Revue belge de musicologie, 1951)
Keywords: park

L'abbaye norbertine du Parc-Le-Duc : huit siècles d’existence, 1129-1929 - Jansen, Joseph Evermode (Dessain, 1929)
Keywords: park

Les anciennes cures de Parc - Nols, Quirin (Analecta Praemonstratensia, 1929)
Keywords: park

Les chartes de fondation de l'abbaye du Parc - Versteylen, J. A. (Analecta Praemonstratensia, 1929)
Keywords: park

L'"Epistola reformatoria" du prieur de Bethléem Henri van der Heyden pour l'abbaye du Parc au XVe siècle - Heyden, Henri van der (Imprimerie de l'abbaye, 1927)
OCLC: 480159683
Keywords: park

Thierry van Tuldel et la commende en Brabant. 1470-1490 - Erens, Ambrosius (Analecta Praemonstratensia, 1925)
Keywords: park; 🇧🇪 belgium (general)

Status monasterii Parcensis (1280-1329) - Waefelghem, Raphaël van (Bulletin de la Commission Royale, 1923)
Keywords: park

Une élection abbatiale au XVe siècle. Thierry de Thulden, abbé du Parc (1462) - Waefelghem, Raphaël van (Mélanges d'histoire offerts à Charles Moeller : à l'occasion de son jubilé de 50 années de professorat à l'Univ. de Louvain, 1863-1913, 1914)
Keywords: park

Les cartulaires de l'abbaye du Parc - Waefelghem, Raphaël van (Misch et Thron, 1909)
Keywords: park

Le Nécrologe de l'abbaye du Parc - Waefelghem, Raphaël van (Misch et Thron, 1908)
Keywords: park

Notitia relatant quelques une des premières donations à l'abbaye du Parc - Nélis, Hubert (Analectes de l'Ordre de Prémontré, 1906)
Keywords: park

Cartae Parcense - De Marneffe, E. (Bijdragen tot de Geschiedenis, bijzonderlijk van het aloude Hertogdom Brabant, 1905)
Keywords: park

Cartae Parcense - De Marneffe, E. (Bijdragen tot de Geschiedenis, bijzonderlijk van het aloude Hertogdom Brabant, 1904)
Keywords: park

Cartae Parcenses - De Marneffe, E. (Bijdragen tot de Geschiedenis, bijzonderlijk van het aloude Hertogdom Brabant, 1903)
Keywords: park

Recherches historiques sur l'ancienne abbaye de Parc - Raymaekers, F.J. (Revue catholique: Recueil Religieux, Philosophique, Scientifique, Historique et Littéraire, 1858)
Keywords: park